2021
DOI: 10.11591/ijphs.v10i1.20613
|View full text |Cite
|
Sign up to set email alerts
|

Factors affect the vasectomy uptake of married couples in Bangka Belitung Islands, Indonesia

Abstract: Vasectomy is a highly effective male contraception. However, the 2007 to 2017 Indonesia Demographic and Health Surveys reported no vasectomy cases in Bangka Belitung Islands. This study aimed to identify the number and its barriers to low vasectomy use in the Bangka Belitung Islands. The combination of qualitative and quantitative methods used in this study. This study utilized health clinics’ reports between 2015 and 2018 to identify whether or not vasectomy was executed in Bangka Belitung Islands. In-depth i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Certain side effects of female contraception will always be considered unacceptable for some women, making their husbands play a further role in family planning options (Shattuck, Perry, Packer, & Quee, 2016;Shattuck et al, 2014). A study in Bangka Belitung Islands also confirmed the result that side effect of female contraceptive use is one of substantial factors related to male contraceptive adoption in the Islands (Irawaty & Rafani, 2021).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Certain side effects of female contraception will always be considered unacceptable for some women, making their husbands play a further role in family planning options (Shattuck, Perry, Packer, & Quee, 2016;Shattuck et al, 2014). A study in Bangka Belitung Islands also confirmed the result that side effect of female contraceptive use is one of substantial factors related to male contraceptive adoption in the Islands (Irawaty & Rafani, 2021).…”
Section: Discussionmentioning
confidence: 80%
“…Some researchers argued that the place of residence may influence the male contraception services since most of the health providers tend to stay in urban areas (Ntoimo & Chirwa-Banda, 2017;Ochako, Temmerman, Mbondo, & Askew, 2017). The others suggest male contraceptive use depends on the couples' age (Ochako et al, 2017), the couples' educational attainment (Eeckhaut, 2018;Le Guen et al, 2015), couples' fertility preference (Ntoimo & Chirwa-Banda, 2017), spousal communication on family planning matters (Cynthia, 2011;Shattuck et al, 2011), and side effect of female contraceptive methods (Irawaty & Rafani, 2021).…”
Section: Introductionmentioning
confidence: 99%